Longitudinal integrated clerkships from start to finish: A medical curriculum innovation - Julia Blitz; Ian Couper; Maryke Geldenhuys; Marina Klocke; Maria van Zyl (AOSIS, 2024)
Stellenbosch University embarked on a renewal of its MBChB programme guided by an updated set of core values developed by the multidisciplinary curriculum task team. These values acknowledged the important role of (among others) context and generalism in the development of our graduates as doctors of the future for South Africa. This report describes the overall direction of the renewed curriculum focusing on two of the innovative educational methods for Family Medicine and Primary Health Care training that enabled us to respond to these considerations. These innovations provide students with both early longitudinal clinical experience (now approximately 72 h per year for each of the first 3 years) and a final longitudinal capstone experience (36 weeks) outside the central tertiary teaching hospital. While the final year experience will run for the first time in 2027 (the first year launched in 2022), the initial experience has got off to a good start with students expressing the value that it brings to their integrated, holistic learning and their identity formation aligned with the mission statement of this renewed curriculum. These two curricular innovations were designed on sound educational principles, utilising contextually appropriate research and by aligning with the goals of the healthcare system in which our students would be trained. The first has created opportunities for students to develop a professional identity that is informed by a substantial and longitudinal primary healthcare experience. Contribution: The intention is to consolidate this in their final district-based experience under the supervision of specialist family physicians and generalist doctors.